Does Transfer Pricing, Capital Intensity and Inventory Intensity Affect Tax Avoidance in Mining Sector Companies? - Sukrianingrum, Denisa Rizky; Madjid, Seva; Qudsiyyah, Zayyun Chadhirotul; Suhono, Suhono (YUME : Journal of Management, 2022)
This study aims to find empirical evidence of transfer pricing, capital intensity and inventory intensity on tax avoidance. This study obtained data from the official website of each company and the Indonesian Stock Exchange. The sample in this study used data from 13 mining companies listed on the Indonesian stock exchange in 2016-2020. The sample in this study were selected using the purposive sampling method. The data in this study were analyzed using multiple linear regression analysis with several stages such as classical assumption test, partial test, and simultaneous test using the SPSS application. This study found that transfer pricing and inventory intensity partially have a negative and significant effect on tax avoidance, while capital intensity does not affect on tax avoidance. Simultaneous testing shows that transfer pricing, intensity of capital, and intensity of inventory positively and significantly impact tax avoidance in mining companies listed on the Indonesia Stock Exchange.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//